Self protection and stop bullying campaign for kids at RPTRA Sungai Bambu, Tanjung Priok, Jakarta Utara - Mansur, Suraya (ASEAN Journal of Community Engagement, 2020)
This paper presents a socialization and counseling program anchored on the themes “self-protection” and “stop bullying.” The program aims to explain the importance of knowing what parts of our body can and cannot be touched by other people, the need to be vigilant when invited to quiet places either by known or unknown people, and how to act in such situations. Bullying is sometimes undetected because it is considered normal or funny. Therefore, children must be told that calling names in the form of ridicule or hitting others is an unjustified action. The methods used in this program are socialization and counseling. The program, which was attended by 50 children, was implemented in the Sungai Bambu Child-friendly Integrated Public Space (RPTRA) Tanjung Priok, North Jakarta on Saturday, December 01, 2018. The children sang “Sentuhan Boleh Sentuhan Tidak Boleh.” (What You Can Touch and What You Can’t Touch) together with their peers. Results show that children who participate in community service activities exhibit an increased level of knowledge and awareness of self-protection by following the instructions in the song.